2014
DOI: 10.1016/j.knee.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

MPFL reconstruction using a quadriceps tendon graft

Abstract: IV, prospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 36 publications
2
30
1
1
Order By: Relevance
“…As the incidence of postoperative episodes of instability increases linearly with time from surgery, 1,23 our results should be interpreted with the understanding that certain studies may have underestimated recurrent instability as a consequence of short follow-up periods. 18,34,40,45,46,71 The Tegner activity scale was designed to assess work and sports activity levels and has been validated in cohorts with patellar instability. 10,59,66 Only 4 of the 14 included studies utilized the Tegner scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the incidence of postoperative episodes of instability increases linearly with time from surgery, 1,23 our results should be interpreted with the understanding that certain studies may have underestimated recurrent instability as a consequence of short follow-up periods. 18,34,40,45,46,71 The Tegner activity scale was designed to assess work and sports activity levels and has been validated in cohorts with patellar instability. 10,59,66 Only 4 of the 14 included studies utilized the Tegner scale.…”
Section: Discussionmentioning
confidence: 99%
“…10,59,66 Only 4 of the 14 included studies utilized the Tegner scale. 11,18,34,45 Two studies 11,45 had patients fill out the scale retrospectively relative to their preinjury condition and demonstrated higher preinjury scores (6.1 and 4.2) than the other 2 studies, 18,34 which collected data prospectively on preoperative conditions (4.8 and 3.0). The mean postoperative Tegner score was 5.7, which is similar to the scores of 5.4 and 5.8 found in recent reviews that examined patients’ ability to return to sports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The revision reconstruction rate was 2.9%. Howells et al 50 Fink et al 52 reported the results of 17 reconstructions using the quadriceps tendon technique. The mean Kujala score at 12 months was 89.2.…”
Section: Discussionmentioning
confidence: 99%
“…The native medial patellofemoral ligament tightens in extension and loosens following 30°to 40°of flexion; therefore, restoration of the native anatomy is critical for a successful outcome. The degree of flexion during fixation has varied in the literature, with a systematic review showing values both below and above 60°of flexion, without a definitive conclusion 50,51 . Because biomechanical studies have shown that the medial patellofemoral ligament has maximum restraint in 30°of flexion, our fixation is tensioned and fixed in 30°of flexion 6,52,53 .…”
Section: Medial Patellofemoral Ligament Reconstruction With Semitendimentioning
confidence: 99%